IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DI KABUPATEN SIMEULUE DALAM MEWUJUDKAN KEMANDIRIAN MASYARAKAT DESA - Sri Wahyu Handayani; Aminah Aminah (Universitas Teuku Umar, 2018)
The purpose of this study is to describe and analyze the implementation of law number 6 of 2014 concerning villages in simeulue district. This study used a qualitative method with descriptive type. The analysis is carried out by relying on the findings of data that has been successfully collected and various relevant information from the literature (secondary data). This research uses van metter van horn's theory and institutional theory. The determination of informants used non-probability sampling techniques so that not all Simeulue District government officials had the same opportunity to be sampled (informants). The results of the study indicate that the implementation of the law on villages in simeulue district in general can be said to be quite good, it can be seen from indicators 1) standards and policy objectives, 2) characteristics of implementing agents, 3) Attitudes (Dispositions) of implementers, 4) Communication between organizations and implementing activities, 5) Economic, social and political environment. Whereas 6) the resources available in Simeulue Regency are still very insufficient in number, especially at the BAPPEDA and DPMD levels, and so are the skills / expertise possessed by village facilitators in the simeulue that are still weak. Keywords: Village, Implementation, Undang-Undang Desa, Government, Simeulue